Birth weight and body fat mass in adults assessed by bioimpedance in the ELSA-Brasil study - Carolina Breda Resende (2021)
Intrauterine life is a critical period for the development of body fat and metabolic risk. This study investigated associations between birth weight and total and truncal body fat in adults. To do so, we analyzed data on 10,011 adults participating in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) who self-reported birth weight as < 2.5kg, 2.5-4.0kg, or > 4.0kg at baseline (2008-2010) and underwent bioimpedance in the next follow-up visit (2012-2014). Greater mean total and truncal fat mass were seen in those with high birth weight compared with adequate birth weight (p < 0.001) in both sexes (total fat: 25.2 vs. 23.1kg in men and 31.4 vs. 27.7kg in women, and truncal fat: 13.5 vs. 12.4kg in men and 15.9 vs. 14.2kg in women). U-shaped patterns were observed in restricted cubic-spline analyses in the subset of 5,212 individuals reporting exact birth weights, although statistically significant only for those with high birth weight. In the whole sample, in comparing high to adequate birth weight, the latter predicted having a large (> 85 percentile) total and truncal fat mass, respectively: OR = 1.76, 95%CI: 1.37-2.25 (men) and OR = 1.86, 95%CI: 1.42-2.44 (women); OR = 1.68, 95% CI: 1.31-2.16 (men) and OR = 1.73, 95%CI: 1.31-2.28 (women). However, low birth weight predicted having a large (> 85 percentile) % truncal fat only in women (OR = 1.40, 95%CI: 1.03-1.91). In conclusion, in these men and women born in a period in which fetal malnutrition was prevalent, birth weight showed complex, frequently non-linear associations with adult body fat, highlighting the need for interventions to prevent low and high birth weight during pregnancy.